2022
DOI: 10.21037/atm-22-5148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-21-3p on lung injury in rats with traumatic hemorrhagic shock resuscitated with sodium bicarbonate Ringer’s solution

Abstract: Background: Restricted fluid resuscitation is the most important early method for treating traumatic hemorrhagic shock (THS). This study sought to explore whether micro ribonucleic acid (miR)-21-3p affected resuscitated THS rats by regulating the glycocalyx and inflammation. Methods: MiRNAs extracted from the lung tissues were analyzed by miRNA microarray assays. A rat model of THS was induced by hemorrhage from a left femur fracture. The pathological change in the lung tissues and glycocalyx structure was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Studies have shown that it has good effects on the supplement of circulating blood volume and the correction of metabolic acidosis (3,4). Evidence sug-gests that BRS has more advantages on effectiveness and safety than LRS in treating THS (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that it has good effects on the supplement of circulating blood volume and the correction of metabolic acidosis (3,4). Evidence sug-gests that BRS has more advantages on effectiveness and safety than LRS in treating THS (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous microRNA microarray showed that miR-21-3p was aberrantly expressed in THS rats and THS/R rats, and miR-21-3p promoted glycocalyx damage, thereby aggravating the lung injury in the THS rats resuscitated with BRS (6). MiR-21-3p has been reported to increase the intestinal epithelial tight junction permeability and promote intestinal barrier dysfunction (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%